Prolific approach for the removal of dyes by an effective interaction with polymer matrix using ultrafiltration membrane. Issue 6 (December 2021) - Sunil, K.; Sherugar, Prajwal; Rao, Srilatha; Lavanya, C.; Balakrishna, Geetha R.; Arthanareeswaran, G.; Padaki, Mahesh
Abstract: The present work reports the effective method for removal of dyes using graphene oxide (GO) and polysulfone (PSf) composite membranes. The membranes were prepared by phase inversion method using PSf with different concentrations of GO ranging from 1% to 4% and polyethylene glycol (PEG 4000 Da) was used as a pore forming agent. The prepared membranes were successfully characterized for their physical and chemical properties, as well as performance ability in terms of dye removal. The presence of GO in the membranes was unambiguously confirmed by ATR–IR spectra and XRD analysis. While pure water flux and rejection studies were carried out using dead–end filtration unit. The rejection experiment was conducted with and without addition of PVA and it was found that, PVA enhanced the rejection up to 100%. Evidently, 2% GO incorporated membrane demonstrated better rejection compared with other membranes. The process is able to remove 100% Methyl Orange, Methylene Blue, Sulfone Black F, Rhodamine 6G and Malachite Green dyes. Effect of pressure, pH, and time duration on filtration is reported and more effect performance was observed. The probable mechanism for separation of organic dyes was predicted. Finally, industrial dye effluents were also subjected for rejection experiment and 58–68% of rejection was observed. The addition of PVA to dye solution was found as an effective interaction method for removal of dyes using membrane technology. Graphical Abstract: ga1 Highlights: Graphene Oxide incorporation enhanced the membrane performance. Addition of PVA to feed is enhanced the dyes rejection. Hydrophilic membrane is more effective. Removal efficiency is depending on pH.